Flexibility in metal forming. Issue 2 (2018) - Yang, D.Y.; Bambach, M.; Cao, J.; Duflou, J.R.; Groche, P.; Kuboki, T.; Sterzing, A.; Tekkaya, A.E.; Lee, C.W.
Abstract: Flexibility in metal forming is needed more than ever before due to rapidly changing customer demands. It paves the way for a better control of uncertainties in development and application of metal forming processes. Although flexibility has been pursued from various viewpoints in terms of machines, material, process, working environment and properties, etc., a thorough study of the concept was undertaken in order to with problems of manufacturing competiveness and tackle new challenges of manufacturing surroundings. Therefore, in this paper, flexibility in forming is reviewed from the viewpoints of process, material, manufacturing environment, new process combinations and machine–system–software interactions.